Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1115/1.2831194
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Periodic Trajectories for Optimal Robot Excitation

Abstract: This paper describes the parameterization of robot excitation trajectories for optimal robot identification based on finite Fourier series. The coefficients of the Fourier series are optimized for minimal sensitivity of the identification to measurement disturbances, which is measured as the condition number of a regression matrix, taking into account motion constraints in joint and cartesian space. This approach allows obtaining small condition numbers with few coefficients for each joint, which simplifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 2 publications
0
18
0
1
Order By: Relevance
“…As mentioned in the introduction, parameterizing the trajectory in the form of finite Fourier series analytical functions brings many advantages. It was initially introduced by Swevers et al [15] and widely implemented afterwards. It has the following analytical form:…”
Section: Trajectory Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, parameterizing the trajectory in the form of finite Fourier series analytical functions brings many advantages. It was initially introduced by Swevers et al [15] and widely implemented afterwards. It has the following analytical form:…”
Section: Trajectory Optimizationmentioning
confidence: 99%
“…To discard these disadvantages, Swevers et al [15] suggested considering the configurations governed by a single global trajectory. This trajectory is parameterized using a finite Fourier series function, its coefficients being the variables of the optimization process.…”
Section: Introductionmentioning
confidence: 99%
“…For the robotic manipulator, the identification results of the dynamic parameters rely on excitation trajectories [28,29]. In our identification experiment, the excitation trajectory of the parallel manipulator is designed in the workspace.…”
Section: Identification Experimentsmentioning
confidence: 99%
“…18 However, their optimization process requires a set of optimized sampled configurations that must obey the kinematic constraints of the mechanical structure at all levels, which is difficult to achieve. Swevers et al 19 then proposed a dynamic parameter identification method using a single global trajectory that is parameterized using a finite Fourier series function. Because of the advantage of obtaining the velocities and accelerations in the frequency domain from the analytical derivation of the designed Fourier series trajectory and reducing the noise-to-signal ratio by averaging the measurement data obtained for more than one cycle, this method has received more attention in recent identification processes; see for example.…”
Section: Introductionmentioning
confidence: 99%